PENGARUH RETURN ON ASSET (ROA), RETURN 0N EQUITY (ROE), DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PT BANK NEGARA INDONESIA (PERSERO) Tbk PERIODE 2012-2021 - Seri Wahyuni, Eka; Febrianti, Sukma (Jurnal Ekonomi STIEP, 2023)
This study aims to determine the effect of Return On Asset (ROA), Return On Equity (ROE), and earnings per Share (EPS) on Stock Price. The data used in this study are associative Quantitative data. The type of data used in this study is secondary data obtained from financial statements published in the financial statements and annual reports of banking companies listed on the Indonesia Stock Exchange through the official website of PT Bank Negara Indonesia Persero Tbk for the 2012-2021 period, and www.idx.co.id, www.idn.financial.com. Data collection techniques in this study used documentation techniques. Data analysis techniques use descriptive statistical tests, classical assumption tests, multiple linear regression and hypothesis tests, namely f test, t test and coefficient of determination test (R2) with Eviews 10 tools. The results showed that simultaneously (F test) all variables ROA, ROE and EPS had a significant effect on stock prices as evidenced by the prob (F-statistical) value of 0.000031 < 0.05. And the partial sacra (t test) of the ROA variable has a significant effect on the stock price as evidenced by a significance value smaller than 0.05, namely 0.0004 < 0.05 and the ROE variable has a significant effect on the stock price with a significance value of 0.0002 < 0.05 as well as the EPS variable showing a significant effect on the stock price with a significance result of 0.0189 < 0.05.